The use of self-inflating soft tissue expanders prior to bone augmentation of atrophied alveolar ridges - Mertens, Christian; Thiele, Oliver C.; Engel, Michael; Seeberger, Robin; Hoffmann, Jürgen; Freier, Kolja (Clinical implant dentistry and related research, 2015)
BACKGROUND: Extensive bone augmentation procedures are frequently performed prior to implant surgery. To achieve tension-free wound closure at the grafted site and thus avoid dehiscence and exposure or total loss of the bone graft, extensive soft tissue mobilization is required.In vitro studies have shown the potential of self-filling osmotic tissue expanders to optimize the amount of resulting soft tissue and vascularization of the recipient site.PURPOSE: The purpose of this prospective clinical study was to evaluate the application and complication rate of osmotic hydrogel expanders inserted subperiosteally prior to bone grafting. METHODS: In this prospective observational study, eight patients were implanted with 11 intraoral osmotic hydrogel expanders prior to bone augmentation procedures. All expanders were placed in subperiosteal positions using the tunnel technique. The occurrence of soft tissue-related complications such as necrosis, perforation, infection, or wound dehiscence leading to expander loss was defined as the primary parameter for analysis and evaluation. Further clinical parameters were soft tissue quality and quantity as well as expansion duration. RESULTS: The expansion time depended upon defect size and expander dimensions. Complications, that is, perforation of the expanders through the oral mucosa, occurred in two patients (3 expanders) who suffered from extreme preoperative scarring in the treated areas owing to prior trauma in one patient and cleft surgery in the other. Patients were grafted with autologous (n = 7) or synthetic (n = 1) block grafts. The expanders were removed during bone grafting surgery. No further dehiscence occurred during the observation period, and all patients were treated successfully with dental implants and subsequent prosthetic reconstruction. CONCLUSIONS: Within the limits of this observational clinical study, hydrogel expanders may help to generate additional soft tissue, and they might contribute to the overall improvement of the bone augmentation process by reducing the risk of complications related to the lack of soft tissue. Further randomized controlled studies are necessary.